2020
DOI: 10.1021/acs.analchem.0c01258
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Dipeptide Profiling and Quantitation by Capillary Electrophoresis and Liquid Chromatography Coupled with Tandem Mass Spectrometry

Abstract: Dipeptides have attracted much attention as post-amino acids with physical properties and functions different from those of amino acids. However, a given dipeptide cannot be distinguished by mass spectrometry from its structural isomer with an opposite amino acid binding order unless these isomers are separated before introduction, which complicates the comprehensive analysis of dipeptides. Herein, a novel analytical platform for dipeptide analysis by capillary electrophoresis tandem mass spectrometry and liqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 26 publications
0
27
0
Order By: Relevance
“…In this study, we performed a comprehensive dipeptide analysis of paired tumors and surrounding nontumor liver tissues obtained from 13 patients with HCC and three patients with metastatic liver cancer. We successfully quantified 236 dipeptides (14 overlapped) with our previously developed method using LC-MS/MS and CE-MS/MS [16]. This study reports the largest number of dipeptides detected in the liver tissue to date.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…In this study, we performed a comprehensive dipeptide analysis of paired tumors and surrounding nontumor liver tissues obtained from 13 patients with HCC and three patients with metastatic liver cancer. We successfully quantified 236 dipeptides (14 overlapped) with our previously developed method using LC-MS/MS and CE-MS/MS [16]. This study reports the largest number of dipeptides detected in the liver tissue to date.…”
Section: Discussionmentioning
confidence: 98%
“…Comprehensive dipeptide analysis was performed by CE-MS/MS and LC-MS/MS, as described previously [16]. The CE-MS/MS system was composed of an Agilent 1600 CE system (Agilent Technologies, Santa Clara, CA, USA), Agilent 6490 triple quadrupole mass spectrometer, Agilent 1200 series isocratic HPLC pump, and Agilent G1607A CE-ESI-MS sprayer kit.…”
Section: Dipeptide Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, glutathione is also known as an antioxidant for the cellular detoxification of ROS in the brain [ 45 , 204 ]. Recently, Ozawa et al developed a method for the comprehensive analysis of dipeptides and showed that the profiles of dipeptides in the body were greatly altered in diseases such as cancer [ 205 , 206 ]. Clarifying the dynamics of dipeptides in food and the body will be important to elucidate the mechanism of cognitive decline.…”
Section: Role Of Functional Food Compounds In Cognitive Performancementioning
confidence: 99%